(untitled) (NAU Journal of Library and Information Science, 2022)
Job performance is a significant factor that affects the viability of an organization, particularly the university library. Employees of an organization will make more progress in their job performance if they possess high level of self-efficacy and motivation. The main objective of this study was to determine selfefficacy and motivation as correlate of job performance among librarians in university libraries in South South Nigeria. Three research questions and two hypotheses were formulated to guide the study. The study adopted correlation research design. Population of the study comprised 170 librarians in federal and state university libraries in South South Nigeria. The entire population was studied due to the relatively small size of the population. Questionnaire was the instrument for data collection. Inferential statistics was used to analyze the data collected. Findings of the study show that librarians possessed high level of selfefficacy. The findings also revealed that positive relationship existed between librarians’ self-efficacy and their job performance. The findings further revealed that positive relationship existed between librarians’ self-efficacy, motivation and their job performance. The relationship was also significant. The study recommend that librarians should be sponsored to participate in capacity building workshops to enhance their professional development.